MANAJEMEN SUMBER DAYA MANUSIA, SARANA PRASARANA DAN DANA PENDIDIKAN DI MTS NU BANAT KUDUS - Muna, Faizul; Al Khoiron , Muhamad Fiqhussunnah; Putri , Yulita; Nurhuda , Abid; Sinta , Dewi; Lathif , Nur Muhammad (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2024)
Dynamic leadership in managing human resources, infrastructure, and funds in rural madrasahs has a crucial role in improving the quality of education in the current era. Therefore, this study aims to analyze the characteristics of resource management, infrastructure, and funds at MTS NU Banat Kudus, to become a reference example. This research uses a qualitative approach by analyzing student recruitment policies, management of learning facilities, and allocation of madrasah funds. The results show that the management at MTS NU Banat Kudus includes human resource management which is focused on improving the quality of students through strict selection based on academic and moral abilities. Then the management of infrastructure facilities is carried out by routine monitoring and submitting proposals for repair or addition of facilities needed. In addition, it also includes fund management according to DIPA and BOS regulations, where the BOS funds can be used for school operations and meet various school needs coupled with donations from teachers and parents of students to maximize the optimal use of funds.